The Development of Textbook of Dance Drama Studiesfor Elementary School for PGSD Studies Program in Surakarta, Indonesia - Endang, Slamet St. Y, Winarni, Retno Sri Markamah, (Social Science Learning Education Journal, 2016)
The purpose of this research to develop of dance drama studies texbook for elementary school by using the base elementary character education for students of Elementary School Teacher Study Program (PGSD).This study uses the design of R & D (Research and Development) of the model Borg and Gall (2003), in four stages: exploration, product development, testing the effectiveness of the product, and dissemination.The research was conducted in six PGSD in Central Java, Indonesia. The experiment was conducted twice: December 2015-January 2016 to the exploration stage and March-May 2016 for the development and testing of the effectiveness of the product.This research resulted in several findings: (1) the exploration phase to produce a needs analysis to prototype textbook writing scripts dance drama education in primary schools; (2) the development stage to produce a textbook writing scripts dance drama education in primary schools through the preliminary field testing; (3) stages of testing the effectiveness of textbooks (main field testing) results show that the t-test = 5.427; and manual t count = 5.397 (p = 0:05; t-table = 1.671).H0rejected and significant research. This means Textbooks for Drama DanceResearch for elementary school is effective.